Electronic Resident Card-Making Services (KTP-el) - Nazaruddin, Nazaruddin; Harahab, Tri Winarti; Maryam, Maryam; Alfiady, Teuku (LPPM Universitas Malikussaleh, 2022)
Based on Constitution no. 25 of 2009 concerning public services are all forms of activities in a series of fulfilling service needs for every citizen, both goods, services, and administrative services provided by public services. In the implementation of public services, there are still problems that cause people's lack of satisfaction, as is the case in the management of KTP-el which until now cannot be applied according to the specified procedure. This study aims to determine the quality of service in making KTP-el in Kabupaten Padang Lawas Utara. The research method used is descriptive qualitative method, with nine informants in the study with data collection techniques, namely observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and conclusion. Based on the results of research on the quality of service in making KTP-el in Kabupaten Padang Lawas Utara seen from the (tangible) it is quite good in service facilities and infrastructure to the community, the (reliability) is good in providing services to the community, although training is needed for the community. officers to improve skills, the dimension of assurance (guarantee) is not good in the timeliness of issuing KTP-el to the public, empathy (empathy) in service there are still discriminatory services (discrimination) to the community. It is hoped that The quality of service for making KTP-el in North Padang Lawas Regency can be further improved to create satisfying services for the community.